2020
DOI: 10.1029/2019gl084354
|View full text |Cite
|
Sign up to set email alerts
|

Explanation for the Increase in High‐Altitude Water on Mars Observed by NOMAD During the 2018 Global Dust Storm

Abstract: The Nadir and Occultation for MArs Discovery (NOMAD) instrument on board ExoMars Trace Gas Orbiter measured a large increase in water vapor at altitudes in the range of 40-100 km during the 2018 global dust storm on Mars. Using a three-dimensional general circulation model, we examine the mechanism responsible for the enhancement of water vapor in the upper atmosphere. Experiments with different prescribed vertical profiles of dust show that when more dust is present higher in the atmosphere, the temperature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
95
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 32 publications
13
95
1
Order By: Relevance
“…Moreover, peak cloud altitudes are slightly higher during the onset of the GDS than reported in non‐GDS years. Indeed, models (Neary et al, ) showed that GDSs are expected to slightly increase the average and maximum altitude of water ice clouds, which is consistent with our observations. The sharp increase in water ice cloud altitude observed during the GDS indeed confirms that this water ice cloud increase is directly connected to dust storm activity.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, peak cloud altitudes are slightly higher during the onset of the GDS than reported in non‐GDS years. Indeed, models (Neary et al, ) showed that GDSs are expected to slightly increase the average and maximum altitude of water ice clouds, which is consistent with our observations. The sharp increase in water ice cloud altitude observed during the GDS indeed confirms that this water ice cloud increase is directly connected to dust storm activity.…”
Section: Resultssupporting
confidence: 92%
“…We note that the above behavior appears to be relatively uniform around the planet (i.e., both zonally and meridionally). Specifically, in the southern hemisphere, even though the observed latitude varies from 74 S to 5 S between Ls=219 and Ls=241, one does not see a change in both the haze top altitude and the maximal altitude of the water ice clouds; in agreement with the simulations presented in Neary et al (, Figure ). We nonetheless identify a temporal trend likely related to the progressive decay of the dust storm (Guzewich et al, ): From Ls=220 to Ls=243, the lower altitude of the detected water ice clouds in the southern hemisphere decreases from 68 to 54 km (cf.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations